SURVEI JENTIK NYAMUK AEDES AEGYPTI DI WILAYAH KERJA PUSKESMAS PASIRKALIKI RW 03 KELURAHAN PASIRKALIKI, KECAMATAN CIMAHI UTARA (Poltekkes Kemenkes Bandung, 2023)
ABSTRACT Indonesia is a country with high cases of dengue fever, this is due to the ideal tropical climate conditions for the development of dengue mosquitoes. The problem in this service is how to reduce the high number of dengue cases.ObjectiveThis community service is to look at the density of the House Index, Container Index, and Breteau index larvae.Method service is survey and observation.Results : RT 01 : House Index 44,4 %, Container Index 24,6% ,RT 02 : House Index 22,2 %, Container Index 18,4 %, RT 04 : House Index 14,4 %, Container Index 29,7 % , RT 05 : House Index 22,7 % ,Container Index 2.5 % Breteau Index RW 03Density Figure 6, with a value of 69.4% can be categorized as high density. The mapping results can be interpreted that the presence of larvae in containers in the western and northern areas of RW.03 can be a risk for larvae to breed into adult mosquitoes that can transmit vector-borne viruses. The surrounding areas that are at risk of transmitting vector-borne diseases from west to east include RW. 10, 02, 04 13 and 12.Conclusion RT 01 House Index andHouse Index high category, RT 02 :House Index andHouse Index medium density category, RT 04: House Index medium density category,House Index high category., RT 05 :House Index andHouse Index medium category. The Breteau Index RW 03 with a value of 69.4% is in the high category Keywords: Survey, mosquito larvae, Aedes Aegypti